Developing and Validating a Novel, Culture-Fair Assessment of Fluid Intelligence: A Multimodal Approach Combining Neuroimaging and Behavioral Measures in Indonesia - Eva Naritawati; Vita Amanda; Wisnu Wardhana Putra; Moon Kaeun (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Fluid intelligence (Gf) is a critical cognitive ability, but its assessment is often biased by cultural and educational factors. Existing Gf tests developed in Western contexts may not be valid in diverse populations like Indonesia. This study aimed to develop and validate a novel, culture-fair Gf assessment tool (the